Analisis Unsur Intrinsik Cerpen Laki-Laki Sejati Karya Putu Wijaya - Yuda Saputra; Wini Yuniar Pusparani (Kajian Administrasi Publik dan ilmu Komunikasi, 2024)
The short story Laki Sejati by Putu Wijaya is one of the works of Indonesian literature that depicts the dynamics of human life and internal conflicts. This research aims to analyze the intrinsic elements in the short story, including themes, characters and characterization, plot, setting, point of view, and mandate. Through this analysis, it is revealed how these intrinsic elements are used by the author to build a story that is evocative and full of meaning. The results of the analysis show that the main theme of this short story is the search for identity and the true meaning of "masculinity". The main character, who has an inner struggle in understanding the values of masculinity, is shown with a deep complexity of character. The progressive storyline with intense conflict takes the reader on the emotional journey of the main character, while the physical and social setting reinforces the realism of the story. A limited third-person perspective is used to explore the main character's perspective, revealing the inner dynamics that are the main focus of the story. The mandate contained in this short story invites readers to reflect on the true meaning of identity, courage, and happiness in life. This study concludes that the intrinsic elements in the short story Hukum Hukum are used very effectively to describe the struggle of human beings in understanding their identity. This short story is not only a literary work, but also a philosophical reflection on life and the meaning of masculinity.